Gratitude Questionnaire–20 Items (G20): A Cross-Cultural, Psychometric and Crowdsourcing Analysis - Bernabe-Valero, Gloria; Blasco-Magraner, José S.; García-March, Marianela R. (Frontiers in Psychology, 2020)
The use in psychology of crowdsourcing platforms, as a method of data collection, has been increasing in popularity because of its relative ease and versatility. Our goal is to adapt the Gratitude Questionnaire - 20 Items (G20) to the English language by using data collected through a crowdsourcing platform. The G20 is a comprehensive instrument that takes in consideration the different basic processes of gratitude and assesses the construct's cognitive, evaluative, emotional and behavioral processes. We test the psychometric properties of the English version of the G20 with a Prolific (ProA) user sample. We assess the adequacy of the G20 for the crowdsourcing population in its English version. A description of the characteristics of the participants is conducted. Reliability analyses reveal an optimal internal consistency of the adapted scale. The results are discussed from a cross-cultural vision of gratitude. We conclude that the Gratitude Questionnaire – 20 Items (G20) adapted to English with an American sample, is a psychometrically strong instrument to measure gratitude using crowdsourcing platforms for data collection and, therefore, a reference and useful tool in future research.